Culturing strategy for producing levan by upcycling oil produced water effluent as base medium for Zymomonas mobilis. (April 2022) - Santos Ferreira, Joalene de Azevedo; Sampaio, Igor Carvalho Fontes; da Cruz Hora, Carolaine Ellen; Torres Lima Matos, Josilene Borges; de Almeida, Paulo Fernando; Chinalia, Fábio Alexandre
Abstract: Three distinct reported media were tested as organic and inorganic supplementation of produced water (PW) from mature oil wells with the aim of producing levan. This effluent is generated at high amounts during oil extraction and are often associated to significant environmental impact and treatment costs. PW may display significant amounts of salts that can hinder microbial growth. Using a high saline PW (8%) this research identified that higher sucrose concentrations in association with ammonium and magnesium sulfates mitigated the negative effect of high salts concentrations on Zymomonas mobilis production of levan. Using neat supplemented PW as medium generated within 24 h 10 g L −1 of levan. The highest production of 31.9 g L −1 was obtained with dialyzed pretreated PW. Dialysis pretreatment may be an important standardization of PW prior to full-scale application. FT-IR characterization shows no significant differences between the produced levan and the commercial counterpart. Graphical Abstract: ga1 Highlights: Sucrose, (NH4 )2 SO4, MgSO4 in oil produced saltwater (PW) favors levan production. Levan yields on pretreated PW were similar to obtained with synthetic medium. Bioreactor operating strategy reduced the levan production period to 24 h. PW pretreatment and amendments may affect long-term levan yield and process stability.